The Maverick club legend (Cimarron, New Mexico Cimarron Legend, 1992)
Article on how the Maverick club was started in 1922 and its purpose. There is also a calendar of events for 1992.
Master List item # 5
File location is in the Raton File Cabinet
Keywords: The Maverick Club; Kiwanis Club; Lions Club; Local History; Clubs; Rodeo; Membershiip; Charitable Activities; Ladies Night Dinner; Cimarron, New Mexico